Innovative Tin and hard carbon architecture for enhanced stability in lithium-ion battery anodes - Shahzad, Rana Faisal (2024)
Tin (Sn), with a theoretical capacity of 994 mAh g-1, is a promising anode material for lithium-ion batteries (LIBs). However, fundamental limitations like large volume expansion during charge-discharge cycle and confined electronic conductivity limit its practical utility. Here, we report a new material design and manufacturing method of LIB anodes using Sn and Hard Carbon (HC) architecture, which is produced by Physical Vapor Deposition (PVD). A bilayer HC/Sn anode structure is deposited on a carbon/copper sheet as a function of deposition time, temperature, and substrate heat treatment. The developed anodes are used to make cells with a lithium-ion electrolyte using a specific fabrication process. The morphology, atomic structure, conductivity, and electrochemical performance of the developed HC/Sn anodes are studied with SEM, TEM, XPS, and electrochemical techniques. At a discharge rate of 0.1C, the Snheated + HC anode performs exceptionally well, offering a capacity of 763 mAh g-1. It is noteworthy that it achieves a capacity of 342 mAh g-1 when fast charging at 5C, demonstrating exceptional rate capability. The Snheated + HC anode maintains >97 % Coulombic efficiency of its capacity after 3000 cycles at a rate of 0.1C after 3000 cycles 730.5 mAh g-1 recorded, demonstrating an impressive cycle life. The novel material design approach of the Snheated + HC anode, which has a multi-layered structure and HC acting as a barrier against volumetric expansion and improving electronic conductivity during battery cycling, is perceived as influential in uplifting anode's performance.